Bifurcação de Turing-Hopf em um sistema presa-predador - Farias, Luiz Eduardo Rosa (2012)
In this work we studing a generalized predator-prey system in a spatial domain, in terms of formation. We show parameter, regions where transcritical, Hopf and Turing bifurcations appear are presented, and also some spatial patterns that arise for specific parameters in the Turing region are also shown.